Implementasi Program Bimbingan Perkawinan dalam Meminimalisir Perceraian (Studi Kasus KUA Kecamatan Kota Kabupaten Pamekasan) - nur hotimah hotimah (Sekolah Tinggi Agama Islam Publisistik Thawalib Jakarta, 2021)
Marriage guidance is one of the programs held by the government to make married couples have a sakinah mawaddah warohmah family life. This program aims to provide an understanding of prospective married couples about the sciences related to domesticity in the hope that prospective couples can have provisions in navigating the household ark. The type of research used by the author in looking at this phenomenon is descriptive-qualitative. The data collection was done through interviews, observation and documentation. The research location is in KUA Pamekasan District. While the subjects in this study were five participants of marriage guidance, three organizers and two presenters who were selected using purposive sampling. The results of this study indicate that the implementation of the marriage guidance program in KUA Pamekasan District has been carried out well. However, the implementation has not been in accordance with the existing guidelines because the organizers are trying to adapt to the existing conditions in the Pamekasan sub-district. Regarding the relationship between marriage guidance programs and divorce cases, there is a very close correlation because this program is one of the programs held by the government in preventing or minimizing the occurrence of divorce.